Antimicrobial property and gc-ms analysis of Xylaria Carpophila (pers.) Fr. (Funded Work) - NANDAN PATEL K J,; KRISHNAPPA M, (International Journal of Pharma and Bio Sciences, 2017)
The sporocarps of Xylaria carpophila were collected from fruits of Xylia xylocarpa. Physicochemical were analysed and results revealed highest percentage of water soluble extractives followed by ash content. Alcohol soluble extractive were 10.76%, total moisture content (5.9%) and foreign matter (0.6 %). Extraction was done by Soxhlet apparatus using petroleum ether, chloroform and ethanol, the extract were subjected for qualitative phytochemicals analysis revealed the presence of alkaloids, tannins, flavonoids, sterols, glycosides, terpinoids and phenols. GC-MS analysis of ethanoic extract showed many bioactive compounds. Anti-microbial potentials were studied against pathogenic bacteria and fungal strains. Results revealed the extracts were effective against bacteria but failed to show inhibitory activity against the tested fungal strains.